Enzymatic synthesis of diacylglycerol from palm kernel oil and soy-canola oil blend, and its anti-obesity effects in C57BL/6N mice - Tang, Teck Kim (2013)
The anti-obesity effect of long chain unsaturated diacylglycerol (DG) oil have been well studied but not for short or medium chain saturated DG. Intake of different chain length and degree of saturation of fatty acid in the form of triacylglycerol has different impact on the body. Besides, fatty acid in the form of DG with different chain length and degree of saturation may have different health effect on the body. Therefore, in this study, two types of DG were produced from 1) palm kernel (PK) oil of medium chain saturated fatty acid and 2) soy-canola (SC) blend oil of long chain unsaturated fatty acid through enzymatic glycerolysis process and its health effect was investigated in C57BL/6N mice. The palm kernel diacylglycerol (PKDG) and soy-canola diacylglycerol (SCDG) were produced in 10L pilot-scale packed reactor. The present study involved the determination of the equilibrium time for the optimum reaction PKDG and SCDG while other parameters: glycerol to oil ratio (1.45:10 for PK and 1:10 for SC), temperature (65oC) and enzyme (Novozyme 435 lipase, 8% w/w) substrates ratio were kept constant. The result showed that optimum reaction times for DG production for PKDG and SCDG were 9 hours and 10 hours respectively and is utilized in pilot scale production. Ten batches of PKDG and SCDG were successful produced giving yield of 40% DG. Consecutively, PKDG purification was carried out in 10L short path distiller. The optimum temperature to remove free fatty acid and monoacylglycerol from crude PKDG was 200oC while optimum temperature and maximum recovery of PKDG from crude PKDG was at 250oC with flow rate fixed at 1.008 l/h, roller wiper speed at 280 rpm. Purity for PKDG obtained was 88.77% and percentage of recovery was 74%. The purified PKDG and SCDG were incorporated into animal feed and their dietary effect in diet-induced obese C57BL/6N mice was investigated. Sixteen weeks feeding trial on C57BL/6N mice with high fat diet consisting of 30% PKDG and 30% SCDG were found to significantly reduce the fat accumulation in epididymal and retroperitoneal region as compared to high fat diet 30% palm kernel TG (PKTG) although there were no significant difference (P<0.05) in body weight. Serum glucose, cholesterol, leptin and insulin were significantly suppressed by PKDG and SCDG compared to PKTG. No significant differences (P<0.05) were found in the health benefit effects between PKDG and SCDG. Compared to TG, the structural differences in DG is the main factor contributing to its anti-obesity effect. Fatty acid composition doesn’t seem to influence this ability. In terms of gene expression PKDG induced the high expression of acyl-CoA synthase long chain (ACSL) and acyl-CoA synthase medium chain mRNA in small intestine while SCDG diet induced the high expression of ACSL in liver as well as small intestine suggesting that difference in fatty acid composition (FAC) of DG may potentially induce β-oxidation in different organs in mice. On the other hand, PKDG and SCDG-fed mice showed reduction expression of apolipoprotein B mRNA and have potential to reduce low density lipoprotein level in the body as compared to PKTG. Up-regulation of uncoupling protein-2 in liver and small intestine only can be observed in PKDG-fed mice.